Phosphorus Fertilization Under Different Land Preparation Methods and Performance of Groundnut (Arachis hypogea L.) in Rainforest Zone of Southern Nigeria - Ogeh, Joseph Sunday; Oyibo, Rukeme Orakpogbake (UNIVERSITY OF LAMPUNG, 2014)
A field experiment was conducted on an Arenic paleudult in the rainforest zone of Southern Nigeria to determine the response of an improved variety of peanut (Arachis hypogea L. var. Samnut 23) to phosphorus, under different land preparation methods. Selected land preparation methods were â€œslash and burnâ€ (SB) and â€œslash and mulchâ€ (SM), and the phosphate fertilizer rates were 0, 30, 60, 90 and 120 kg P ha-1.Â The experiment was laid out as a randomized complete by block design. Each land preparation was divided into plots. Macro- and micro nutrient contents of peanut plants were determined, and the growth and yield components were also assessed. Results showed that the pre planting soil analysis for the SB management had a pH of 5.77, N (1.8 gkg-1), P (2.05 mgkg-1) and K (0.11cmol (+) kg-1), while that of the SM had a pH of 5.95, N (0.9 g kg-1), P (0.86 mg kg-1) and K (0.07cmol(+)kg-1).Â Plant height was not significantly different (pdâ€ 0.05) in the land preparation methods, but leaf area was significantly different. However, plant height and leaf area responded better under the SB treatment with 90 kg P ha-1 rate of phosphorus fertilizer than the SM treatment under the same rate. Fresh pod weight of 908.6kg ha-1 and dry pod weight of 558.0kg ha-1 was obtained at 60 kg P ha-1 under the SB treatment and was significantly different from all other treatments including the SM. Significant differences were also observed in the nutrient concentrations of leaves and roots. Highest leaf phosphorus content (3.502 mg kg-1) was recorded at 90kg P ha-1 in the SM treatment while the highest nutrient content of P in the roots (0.272 mg kg-1) was recorded at 30 kg P ha-1 also in the SM treatment. However, the SB treatment recorded the highest peanut seed pods / shell at 60 kg P ha-1. Generally, phosphorus fertilization under the SB management practice gave better results than the SM management practice.Keywords: groundnut, land preparation, phosphorus fertilization, Slash and burn, slash and mulch Â Â [How to Cite: Joseph SO and RO Oyibo. 2014. Phosphorus Fertilization Under Different Land Preparation Methods and Performance of Groundnut (Arachis hypogea L.) in Rainforest Zone of Southern Nigeria. J Trop Soils 19(1): 1-7. Doi: 10.5400/jts.2014.19.1.1] Â